2020
DOI: 10.1177/0305735620917730
|View full text |Cite
|
Sign up to set email alerts
|

Emotions of music listening in Finland and in India: Comparison of an individualistic and a collectivistic culture

Abstract: Music is appreciated for emotional reasons across cultures, but knowledge on the cross-cultural similarities and differences of music-evoked emotions is still sparse. The current study compared music-evoked emotions in Finland and in India, contextualizing them within the perceived psychological functionality of music in an individualistic versus collectivistic culture. Participants ( N = 230) answered an online survey on music-evoked emotions and related personal meanings. A mixed-method approach using factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…Our findings show a universal use of music to obtain wellbeing goals during times of crisis, and by that, extend previous findings for universal functions of music across a large number of traditional communities (Mehr et al, 2019). Indeed, Juslin et al state that although they did find differences between individualistic and collectivistic cultures, these differences were small, such that cross-cultural similarities were larger than cultural differences (see also Saarikallio et al, 2020). Our findings largely echo this claim.…”
Section: Cultural Differences In Uses Of Musicsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings show a universal use of music to obtain wellbeing goals during times of crisis, and by that, extend previous findings for universal functions of music across a large number of traditional communities (Mehr et al, 2019). Indeed, Juslin et al state that although they did find differences between individualistic and collectivistic cultures, these differences were small, such that cross-cultural similarities were larger than cultural differences (see also Saarikallio et al, 2020). Our findings largely echo this claim.…”
Section: Cultural Differences In Uses Of Musicsupporting
confidence: 90%
“…For example, highlight differences in music use for sociocultural functions of national and family identity-partially explained by the Individualistic-Collectivistic dimension (Boer and Abubakar, 2014). Similarly, Saarikallio et al (2020) point to differences between Finns and Indians in functions of music with self-related functions (self-expression, self-enhancement, self-reflective) rated highly by Finns, and mood management goals (relaxation, motivation) more prevalent among Indians. The cultural dimension of Individualistic-Collectivistic was also significant in Juslin et al (2016).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, she suggests three psychological aspects related to music listening which were organized by observing the results of previous studies. The first is the use of music to express, experience, and/or regulate emotions (Juslin and Västfjäll, 2008;Saarikallio et al, 2020); secondly, music is used as a means for reflection, personal development, relaxation, and mental work; and thirdly, music is used as an element to enhance social bonding, social cohesion, and/or identity.…”
Section: Music Listening and Mental Health During The Covid-19 Outbreakmentioning
confidence: 99%
“…Another point is that studies have shown that, in collectivist countries, i.e., Brazil, which prioritizes the group's aims more than an individual's needs, the population uses music to reach relaxation, motivation, and happy states, in contrast with individualist countries where people look for sadnessmelancholy (Juslin et al, 2016;Saarikallio et al, 2020).…”
Section: Music Listening and Mental Health During The Covid-19 Outbreakmentioning
confidence: 99%
“…Additionally, this could also reflect the down-regulation of HAN emotions, where individuals' high-arousal negative emotion states are cathartically released by listening to matching high-arousal music (i.e., discharge regulation: Saarikallio, 2008;Sharman & Dingle, 2015). For collectivistic cultures that prefer low-arousal music, such high-arousal regulatory mechanisms may not be as relevant, as initial evidence suggests that emotion regulation by music occurs through low-arousal relaxation and comfort-related mechanisms instead (Saarikallio et al, 2020). We propose that elucidating these mechanisms could aid our understanding of music preference as a reflection of socio-cultural affordances for emotions.…”
Section: Culture and Music Preferencementioning
confidence: 99%